Prevalence, awareness, treatment and control of hypertension in the Brazilian population and sociodemographic associated factors: data from National Health Survey - Maria Alice Souza Vieira; Luís Antônio Batista Tonaco; Maria José Silva Souza; Flávia Cristina Drumond Andrade; Deborah Carvalho Malta; Mariana Santos Felisbino-Mendes; Gustavo Velasquez-Melendez (BMC Public Health)
Abstract Background Hypertension is the main risk factor for cardiovascular diseases and more recent studies that estimated the prevalence of this condition considering aspects such as awareness of diagnosis, treatment, and control, revealing alarming results in the global scenario. Objective To estimate the prevalence and assess the factors associated with hypertension prevalence, awareness, treatment, and control. Methods This is a cross-sectional study based on data from the 2013 National Health Survey in Brazil. A total of 59,226 individuals of both sexes took part in this study. Exposure were defined based on blood pressure measurements, self-reported diagnosis of hypertension and use of antihypertensive medication. We estimated the prevalence of the dependent variables and the associations were subsequently tested by calculating prevalence ratios using Poisson regression. Results The study population was composed mostly of women (52.3%), aged 36 to 59 years (42.6%), of white race/color (47.5%), with low schooling between 0 and 8 years (49.1%), having a partner (55.7%), in the urban area of the country (86.2%), mainly in the Southeast region (43.9%) and without health insurance (69.7%). The prevalence of hypertension in the Brazilian population was 32.3%. 60.8% were aware of the diagnosis, 90.6% were taking medication treatment and, of these, 54.4% had controlled blood pressure. Female gender and older age were associated with greater awareness (PR 1,34; 95% CI 1,28 – 1,40 / PR 2,40; 95% CI 2,15 – 2,69; respectively), treatment (PR 1,10; 95% CI 1,07 – 1,12 / PR 1,25; 95% CI 1,17 – 1,35; respectively) and control (PR 1,10; 95% CI 1,02 – 1,17 / PR 0,83; 95% CI 0,73 – 0,96; respectively). Other factors such as having a partner, health insurance, living in the urban area, race/color and schooling were also associated with dependent variables. Conclusion This study reveals that although a high percentage of hypertensive patients are taking medication, there are still substantial gaps in awareness and control, particularly among certain sociodemographic groups. Men, those with less schooling, black and brown people, those living in rural areas and those without health insurance have lower levels of awareness and control of hypertension.